Drugs associated with cataract formation represent an unmet need in cataract research - Carlson, Jack; McBride, Kate; O’Connor, Michael (Frontiers in Medicine, 2022)
Decreased light transmittance through the ocular lens, termed cataract, is a leading cause of low vision and blindness worldwide. Cataract causes significantly decreased quality of life, particularly in the elderly. Environmental risk factors, including aging, UV exposure, diabetes, smoking and some prescription drugs, are all contributors to cataract formation. In particular, drug-induced cataract represents a poorly-addressed source of cataract. To better understand the potential impact of prescription drugs on cataract, we analyzed publicly-available drug prescriptions data from the Australian Pharmaceutical Benefits Scheme. The data was analyzed for the 5-year period from July 2014 to June 2019. Analyses included the number of prescriptions for each drug, as well as the associated government and total prescription costs. The drugs chosen for analysis belonged to any of four broad categories—those with known, probable, possible or uncertain association with cataract in patients. The analyses revealed high prescription rates and costs for drugs in the Known category (e.g., steroids) and Possible category (e.g., psychotropic drugs). Collectively, these data provide valuable insights into specific prescription drugs that likely contribute to the increasing annual burden of new cataract cases. These data highlight the need—as well as new, stem cell-based opportunities—to elucidate molecular mechanisms of drug-induced cataract formation.